ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI FUNGSI INTERMEDIASI BANK UMUM DI KOTA BANDA ACEH. - Ratna Mutia, Raja Masbar, Sofyan Syahnur. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2014)
Abstract: This study aims to analyze the factors that influence the intermediary of commercial banks in Banda Aceh . The data used are secondary data from the monthly time series of 2010-2013 and were analyzed by multiple regression method. Based on the research results of the analysis of the effect of interest rates (SB) and Non Performing Loans (NPLs) in the conventional bank acquired 56.01 percent of the dependent variable intermediary (LDR) can be explained by the independent variables and the remaining 43.99 percent of the variation is explained by other variables LDR. SB variables simultaneously and NPL significant effect (real) against the intermediary of commercial banks in the city of Banda Aceh and partially change the conventional banks SB significantly influence the intermediary of commercial banks in the city of Banda Aceh. While the results of research analyzes the effect of revenue sharing (BS) and Non Performing Financing (NPF) in Islamic banks acquired 16.76 percent of variation in the dependent variable Financing Deposit Ratio (FDR) was not able to be explained by the independent variables in the model, while the remaining 83.24 percent is explained by other variables outside the model. BS simultaneously and significant effect NPF and NPF partial effect on the FDR while BS no significant effect on commercial bank in Banda Aceh. The higher the percentage ratio of NPL and NPF indicate progressively worse and the credit quality of financing provided. Will ultimately affect the performance degradation intermediary function of banks is concerned because the bank will be very strict in considering credit financing and banks have to perform the recovery of funds for funds not returned from financing and credit default. Keywords: Interest Rate, Loan to Deposit Ratio (LDR), Financing to Deposit Ratio (FDR), Non Performing Loan (NPL) and Non Performing Financing (NPF). Abstrak: Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi fungsi intermediasi bank umum di kota Banda Aceh. Data yang digunakan adalah data sekunder time series bulanan dari tahun 2010-2013 dan dianalisis menggunakan regresi berganda. Berdasarkan hasil penelitian analisis pengaruh suku bunga (SB) dan Non Performing Loan (NPL) pada bank konvensional diperoleh 56,01 persen variable dependen fungsi intermediasi (LDR) dapat dijelaskan oleh variabel independen dan sisanya 43,99 persen variasi LDR diterangkan oleh variabel lain. Secara simultan variabel SB dan NPL berpengaruh signifikan (nyata) terhadap fungsi intermediasi bank umum di kota Banda Aceh dan secara parsial perubahan SB pada bank konvensional berpengaruh signifikan terhadap fungsi intermediasi bank umum di kota Banda Aceh. Sedangkan hasil penelitian analisis pengaruh Bagi Hasil (BS) dan Non Performing Financing (NPF) pada bank syariah diperoleh 16,76 persen variasi variabel dependen Financing Deposit Ratio (FDR) tidak mampu dijelaskan oleh variabel independen dalam model sedangkan 83,24 persen sisanya dijelaskan oleh variabel-variabel lain diluar model. Secara simultan BS dan NPF berpengaruh signifikan dan secara parsial NPF berpengaruh terhadap FDR sedangkan BS tidak berpengaruh signifikan terhadap bank umum di Kota Banda Aceh. Semakin tinggi persentase rasio NPL dan NPF mengindikasikan semakin buruk kualitas kredit dan pembiayaan yang disalurkan. Pada akhirnya akan berpengaruh terhadap penurunan kinerja fungsi intermediasi bank yang bersangkutan karena bank akan semakin ketat dalam penyaluran pembiayaan dan kredit mengingat bank harus melakukan recovery dana atas dana yang tidak kembali dari pembiayaan dan kredit yang gagal bayar. Kata Kunci: Suku Bunga, Loan to Deposit Ratio (LDR), Financing to Deposit Ratio (FDR), Non Performing Loan (NPL) dan Non Performing Financing (NPF).